Palynofacies and Paleoenvironment investigation of the Hauterivian – Early Aptian Ratawi and Zubair formations, Balad oilfield, Central Iraq - Adnan Q. Mahdi; Fawzi M. Al-Beyati; A. M. Al Tarif; El-Arabi H. Shendi; Mohamed I.Abdel-fattah (Tikrit Journal of Pure Science)
This work depends on a detailed optical observation study of sedimentary organic facies from the Hauterivian – early Aptian Ratawi and Zubair formations from the Ba-1 well, Balad oilfield, Central Iraq. This study has manifested the advantages of palynofacies analysis methods for source rock evaluation of the studied formations, twenty five cutting rock samples organic facies data indicate a wide variation of source richness, quality and thermal maturity, the Ratawi Formation samples has the Type-II< I kerogen indicates marine environment in immature stage, while Zubair Formation has the Type-II<<  I kerogen (oil-gas prone) reflect the marine environment with  terrigenous influx in early mature to mature stage (early oil window).